Objectos subjectivos - Curado, Manuel (2005)
This paper tries to contribute to a second better theory about the hard problem of consciousness. Its main goal is to understand the reason why previous theories have not been succeeded.The intellectual agenda of this strategy can be stated without ambiguity: the knowledge of the systematic and typical errors makes possible a better understanding of the problem. This paper offers a set of conjectures for the solution of the hard problem. The main proposal draws on the indiscernibility between natural subjective experiences and artifkially induced experiences. There is no general argument for these conjectures. That general argument would constitute an optimal theory or a first better theory of the hard problem; however, the main point this paper tries to prove is that there is no optimal solution for the hard problem but only second better strategies. Theories on the hard problem are very different; however, they share common rational limitations. It is possible to formulate reasonable conjectures for the solution of the hard problem taking notice of these rational limitations.